Integrated transcriptomic and proteomic analysis of the immune response in Hyalomma anatolicum to bacterial invasion - Li, Jianlong; Luo, Tingxiang; Ma, Zhen; Yang, Depeng; Yang, Sen; Li, Yongchang; Gailike, Bayinchahan; Guo, Qingyong; Hu, Zhengxiang; Hu, Ercha (Frontiers in Immunology, 2025)
BackgroundHyalomma anatolicum is a multi-host ectoparasite that carries and transmits a variety of zoonotic pathogens. Understanding the immune response of ticks to bacterial infections is of research significance for deciphering their immune defense mechanisms and harnessing tick - derived molecules.MethodsIn the current study, transcriptomic and proteomic analyses on H. anatolicum injected with Staphylococcus aureus (SA group), Proteus mirabilis (PM group) or phosphate buffered saline (PBS group) were performed.ResultsIn pairwise comparisons among the experimental groups, we identified 9,776 (SA/PBS), 10,230 (PM/PBS), and 1,309 (SA/PM) differentially expressed genes (DEGs), as well as 175 (SA/PBS), 277 (PM/PBS), and 223 (SA/PM) differentially expressed proteins (DEPs), respectively. Subsequent KEGG pathway analysis revealed that these DEGs and DEPs were significantly enriched in a range of pertinent pathways, including the immune system and apoptosis, Toll and IMD signaling pathways, MAPK signaling pathway, and NF - κB signaling pathway. The RT - qPCR detection data exhibited a concordant trend with the RNA - seq data, indicating a substantial alignment in the observed results. Notably, the defensin and lectin gene families emerged as potentially pivotal components within the innate immune defense system of ticks.ConclusionOverall, in this study, genes, proteins, and signaling pathways integral to the immune defense of H. anatolicum were identified, offering substantial potential for future research focused on harnessing its intricate immune defense mechanisms for antimicrobial applications.